Meta-análise para estimativas de parâmetros genéticos para características de crescimento em ovinos - Evangelho, Lavínia Aires (2023)
With a growing demand for sheep meat, those produced have increased their productivity and beliefs of genetic parameters such as heritability (direct and maternal) and genetic, phenotypic and environmental correlations are commonly evaluated in domestic animals, including sheep. The aim of this study was to perform a meta-analysis for estimates of direct, maternal and total heritability and genetic correlations for weight gain traits and growth assessments at different ages in beef sheep and to evaluate through a meta-regression the impact of secondary variable on the observed heterogeneity between studies. A search was carried out in the literature of scientific articles published between the years 2012 to 2022 on the digital platforms PubMed, Scielo, Web of Science and ScienceDirect. The random effects model was used to obtain estimates of the combined effects. The effect sizes were evaluated by means of the average of the values published in the literature for the heritabilities and genetic correlations between the evaluated traits. Heterogeneity was reduced using Cochran's I2 and Q statistics. A total of nine traits related to weight gain and growth in sheep were evaluated. A meta-regression was conducted to assess the influence of secondary variables that occurred on the evaluated parameters. After cleaning the data, a total of 118 articles remained for the meta-analysis, which generated 504 heritability estimates and 74 genetic correlation estimates. Pooled heritability estimates across studies ranged from 0.07 to 0.29 for weaning weight and 9-month weight, respectively. The year of data collection, the method and statistics (uni, bi or multivariate) explained the greater proportion of the variability observed between studies. There was a trend towards increased direct heritability for animal weight when the measure was evaluated in older animals, ranging from 0.18 for birth weight to 0.26 for weight at 12 months of age, while maternal heritability decreased with age and ranged from 0.16 to 0.12, for weight at birth and at 6 months of age, respectively, an expected result, given the decrease in the importance of the maternal effect with advancing age, whereas the total heritabilities there was little variation from 0.18 to 0.21 for birth weight and weight at 9 months and for weight at 6 months, respectively. Genetic correlations showed a low variation of 0.45 to 0.53 for birth weight, weaning weight and weight at 9 and 12 months, respectively. The presented results confirm that the growth traits in sheep are subject to selection, being more important at the beginning of the animal's life, which reinforces the hypothesis that it is important to observe, in addition to the effect of the animal's direct genetics, the maternal genetics to carry out more efficient selection, especially for traits measured at younger ages. Moderate correlations suggest a good response to indirect selection, which can be a tool to select traits with lower heritability.